ANALYZING SOCIAL ASPECTS IN THE SCARLET LETTER NOVEL BY NATHANIEL HAWTHORNE (A GENETIC STRUCTURALISM APPROACH) - Sulmi Magfirah (Elite : English and Literature Journal, 2017)
AbstractAnalyzing Social Aspects in the Scarlet Letter Novel by Nathaniel Hawthorne. This research aimed to find out how the structural element of the novel supported the whole idea of the story and the social aspects of Nathaniel Hawthorne novel “The Scarlet Letter”. This thesis is library research and used descriptive method. The object of this research can be divided into two categories, namely primary and secondary data. The data were collected through several techniques, namely read the novel carefully, looked for the difficult word, taking note of the important parts both primary and secondary data, and then read some related literature to support the object that is analyzed. The result of this research show that the social aspects in the scarlet letter novel are divided into five categories, they are: (1) Family, (2) Religion, (3) Tradition, (4) Economy, (5) Education, and this thesis also described the structural elements that support the whole idea of the story.AbstrakAnalisis sosial aspek yang terungkap dalam novel scarlet letter oleh Nathaniel Hawthorne. Penelitian ini bertujuan untuk menemukan struktur elemen yang terdapat dalam novel yang mendukung keseluruhan ide dalam cerita dan aspek social dalam novel “Scarlet Letter” oleh Nathaniel Hawthorne. Penelitian ini adalah bentuk penelitian pustaka dan menggunakan metode deskriptif. Objek penelitian ini terbagi menjadi dua kategori, yaitu data primer dan data sekunder. Data di kumpulkan melalui beberapa tehnik, seperti membaca novel dengan seksama, menemukan kata-kata sulit, mencatat bagian terpenting dari data penelitian, dan membaca beberapa referensi yang berkaitan untuk mendukung objek penelitian yang diteliti. Hasil penelitian ini menunjukkan bahwa aspek social yang terdapat dalam novel Scarlet Letter terdiri dari lima kategori, diantaranya; (1) Keluarga, (2) Agama, (3) Tradisi, (4) Ekonomi, (5) Pendidikan, dan penelitian ini juga menjelaskan struktur elemen yang mendukung semua ide dalam cerita.